Developing holistic models of the structure and function of the soil/plant/atmosphere continuum - Penuelas, Josep; Sardans, Jordi (Plant and soil, 2021)
A model that can assess the structure and functionality of the soil/plant/atmosphere (SPA) continuum along spatial and temporal gradients using specific and measurable variables remains a key objective and challenge in ecological research of terrestrial ecosystems. We analyze the model proposed in this issue by Silva and Lambers (2020) that tries to meet this challenge and further propose complementary points of view to base the model on easy straightforward measurable variables incorporating new recent holistic views of terrestrial ecosystems. Silva and Lambers (2020) explain how symbiotic and competitive strategies involving plants and soil microorganisms through the ecological succession influence scale-free patterns of carbon, nutrient, and water use from individual organisms to landscapes. The algorithms in their model use measurable variables such as specific leaf area (SLA), leaf area index (LAI), stomatal conductance (g), photosynthetic rate (A), gross primary production (GPP), or net primary production (NPP). Other variables, such as the rates of resource depletion or uptake and the level of resources needed to ensure survival, however, are very difficult to determine in the field, impeding the use of these algorithms in some cases. SPA models should thus consider being complemented and reinforced by new emerging holistic approaches and avoid the use of variables that are difficult to measure as much as possible. Integrative approaches such as the biogeochemical niche theory and global C balance, including measurable variables such as bio-elemental composition of soils, microbes and plants should thus be considered.